Muslim Youth and the Negotiation of Identity: Reception Analysis of Popular Culture Content among Muslim Millennials and Gen Z in Urban Areas - Kamilia, Adila (Islamic Journal of Communication and Public Discourse, 2025)
Backround: This research examines the complex negotiation of identity among Muslim millennials and Generation Z in urban settings through the lens of reception analysis theory.Objective: The primary research objective is to analyze how Muslim millennials and Generation Z in urban areas negotiate identity through reception and interpretation of popular culture content.Method: This study employs a mixed-methods approach combining qualitative interviews (n=30) and quantitative surveys (n=500) across three major urban centers. Using Stuart Hall's encoding/decoding model, the research analyzes how Muslim youth interpret and negotiate meanings from popular culture content including social media, streaming platforms, music, and fashion.Findings and Implications: Findings reveal three distinct reception patterns: dominant-hegemonic (23%), negotiated (58%), and oppositional (19%). The negotiated position dominates, indicating that most respondents selectively accept cultural messages while filtering them through Islamic values. Thematic analysis identifies five key identity negotiation strategies: selective engagement, religious reframing, hybrid identity formation, community validation, and digital activism. The research demonstrates that urban Muslim youth actively construct multifaceted identities that integrate religious authenticity with global citizenship. Social media emerges as a critical space where 71% seek spiritual guidance while simultaneously consuming mainstream content.Conclusion: The study contributes to cultural studies and Islamic youth research by documenting how reception processes enable identity fluidity without compromising core religious values. Practical implications suggest that religious institutions should acknowledge youth agency in meaning-making processes and create inclusive spaces that validate hybrid identities.